A Tale of 20 Alphaviruses; Inter-species Diversity and Conserved Interactions Between Viral Non-structural Protein 3 and Stress Granule Proteins - Nowee, Gwen; Bakker, Julian W.; Geertsema, Corinne; Ros, Vera I. D.; Göertz, Giel P.; Fros, Jelke J.; Pijlman, Gorben P. (Frontiers in Cell and Developmental Biology, 2021)
Alphaviruses infect a diverse range of host organisms including mosquitoes, mammals and birds. The enigmatic alphavirus nonstructural protein 3 (nsP3) has an intrinsically disordered, C-terminal hypervariable domain (HVD) that can interact with a variety of host proteins associated with stress granules (SGs). The HVD displays the highest variability across the more than 30 known alphaviruses, yet it also contains several motifs that are conserved amongst different subgroups of alphaviruses. For some alphaviruses, specific nsP3–SG protein interactions are essential for virus replication. However, it remains difficult to attribute general roles to these virus-host interactions, as multiple amino acid motifs in the HDV display a degree of redundancy and previous studies were performed with a limited number of alphaviruses. To better understand nsP3-host protein interactions we conducted comprehensive co-localization experiments with the nsP3s of twenty diverse alphaviruses: Chikungunya, Semliki Forest, Sindbis, Bebaru, Barmah Forest, Getah, Mayaro, Middelburg, O’nyong-nyong, Ross River QML and T48, Una, Whataroa, Southern Elephant Seal, Eilat, Tai Forest (TAFV), Venezuelan/Eastern/Western equine encephalitis (V/E/WEEV) and the aquatic Salmonid alphavirus (SAV), with three different SG proteins (G3BP and its insect homologue Rasputin, FMRP) and BIN1 in mammalian and mosquito cell lines. Despite that all terrestrial alphavirus nsP3s contained at least one BIN1 binding motif (PxPxPR), not all nsP3s co-localized with BIN1. Further, all alphaviruses except SAV, TAFV and VEEV displayed co-localization with G3BP. Although viruses lacking FGxF-like motifs contained Agenet-like domain binding motifs to facilitate interaction with FMRP, cytoplasmic nsP3 granules of all tested alphaviruses co-localized with FMRP. Crispr-Cas9 knockout of G3BP in mammalian cells abolished nsP3-FMRP co-localization for all alphaviruses except V/E/WEEV nsP3s that bind FMRP directly. G3BP knockout also changed nsP3 subcellular localization of Bebaru, Barmah Forest, Getah and Sindbis viruses. Taken together this study paints a more detailed picture of the diverse interactions between alphavirus nsP3 and SG-associated host proteins. The interaction between nsP3 and G3BP clearly plays a central role and results in recruitment of additional host proteins such as FMRP. However, direct binding of FMRP can make the interaction with G3BP redundant which exemplifies the alternate evolutionary paths of alphavirus subgroups.